Pengaruh Penggunaan Bahasa Indonesia Terhadap Pemasaran Produk Kopi Durian Ananda - Sulastri Ningsi; Muhammad Kasoni; Diah Ayu Rahmah (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to identify and analyze the influence of the use of the Indonesian language on the marketing of Durian Ananda coffee products. This research is included in case study research, data collection techniques are carried out by means of interviews and questionnaires. Based on the results of research that has been done to get the following results. There is a significant influence between the use of Indonesian-language brands on consumer perceptions of Ananda durian coffee products. There is a significant influence between advertising on consumers' perceptions of Ananda durian coffee products. There is a significant influence between the media on consumer perceptions of Ananda durian coffee products. There is a significant influence between branding in Indonesian, advertising and media simultaneously (simultaneously) on consumer perception with an F-count value of 23,710 greater than F-table 2.70 and a significance value of 0.000 <0.05, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.